Pengaruh Promosi, Brand Image, dan Lokasi Terhadap Keputusan Pembelian Pada 3Second Store Kediri - Yonas Hans Andreawan; Endah Kurniawati; Nuril Aulia Munawaroh (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study investigates the influence of promotion, brand image, and location on purchasing decisions at 3Second Store Kediri. The research employs a quantitative approach using both primary and secondary data sources. The primary data were obtained through the distribution of questionnaires to 309 respondents, while the secondary data were collected via interviews with store supervisors and direct observation at the research site. The variables under examination include promotion, brand image, and location as independent variables, and purchasing decision as the dependent variable. Data analysis involved both partial and simultaneous hypothesis testing to determine the strength and significance of each variable’s effect. The findings reveal that, partially, each of the three independent variables—promotion, brand image, and location—has a significant and positive effect on purchasing decisions. This indicates that improvement in any of these aspects will lead to a higher likelihood of customers making a purchase. Simultaneous testing also demonstrates that the three variables collectively exert a significant and positive influence on purchasing decisions. Among these, promotion emerges as the most dominant factor affecting purchasing decisions, as confirmed through the partial t-test results. The coefficient of determination (R²) is 0.581, which signifies that 58% of the variation in purchasing decisions can be explained by the three examined variables, while the remaining 42% is attributed to other factors not covered in this study, such as product quality, customer service, and pricing strategies. These results suggest that marketing strategies focusing on well-planned promotional activities, maintaining a strong and positive brand image, and choosing a strategic store location can effectively increase customer purchasing decisions. The findings provide valuable insights for retail management, particularly for fashion retail brands like 3Second Store, in developing targeted strategies to optimize sales performance.